(untitled) (International Journal of Nursing Education, 2020)
Objectives: To compare growth and development outcomes in the interventional and control groups through infancy. Methodology: This prospective, time series, randomized, partially blind, interventional controlled study was conducted from 1st June 2014 to 31st July 2016 at MGM Medical College hospital for Mother and Child Kalamboli, Navi Mumbai, India. Prior approval of the MGMIHS Institutional Ethics Committee was obtained. Inclusion Criteria: Full term newborns with normal vaginal delivery. Pregnant women with single full-term fetus and without any known high-risk pregnancy subjected to their written informed consent. 268 babies each in the intervention group and control group. Babies were randomized to either group, following computer generated random numbers. Data Analysis: Demographic data was analysed by frequency and percentage. Unpaired t tests at respective individual percentiles of P25, P50, P75 and P90 of test items as per DDST-II. Results: Growth and development at 4-6, 8-10, 12-14 weeks; at 6, 9 and 12 months of follow-up. Developmental milestones (DDST-II): Gross motor: Out of total 15 items found relevant under one year of age, the intervention group achieved individual milestones earlier than the control in 6 items and advanced in 3 more items. Language: Advantage of intervention group over control was maintained by I-SUC (Intervention) group in language domain too particularly at 4-6 weeks age (p=0.001) and at one year of age (p=0.005). Fine Motor: Out of 12 items under the broad domains of fine motor development under one year of age, the intervention group achieved several milestones earlier than the control in 4 items. Personal Social: The difference was highly significant at 9 months of age (p=0.005). Conclusion: The I-SUC can safely replace DCC. The great advantage of consistently higher red-cell mass and hemoglobin level through-out in infancy in intervention group all through, on long term follow up till infancy was considered very encouraging.